Electrochemical corrosion of highly conductive Ti-Al-C, (Ti,Mo)-Al-C and (Ti,Cr)-Al-C coatings deposited by hybrid magnetron sputtering using MAX phases-based target - Viktoriia Shtefan; Tetiana Prikhna; Olexandr Kuprin; Viktoriya Podhurska; Orest Ostash; Pavel Potapov; Semyon Ponomaryov; Myroslav Karpets; Volodymyr Sverdun; Viktor Moshchil; Tetiana Serbenyuk (Electrochemistry Communications, 2025)
Amorphous highly conductive coatings Ti-Al-C, (Ti,Mo)-Al-C and (Ti,Cr)-Al-C were deposited on titanium alloy substrates by hybrid magnetron using T2AlC and Ti3AlC2 MAX-phases-based targets and in parallel cathode-arc evaporation of Mo or Cr targets. The (Ti,Cr)-Al-C coating showed the highest electrochemical corrosion resistance among all deposited coatings in 3.5 wt% NaCl aqueous solution at 25 °C: corrosion potential Ecorr = 0.044 V vs. saturated calomel electrode, corrosion current density icorr = 2.48 × 10−9 A/cm2. The (Ti,Cr)-Al-C coating also demonstrated the highest long-term oxidation resistance, and after heating in air at 600 °C for 1000 h, its surface electrical conductivity became even slightly higher after long-term heating: increased from σ = 9.84 × 106 S/m to σ = 4.35 × 105 S/m, which is explained by the crystallization of the amorphous coating during heating process. The nanohardness and Young's modulus of the coating after deposition were within 15 GPa and 240 GPa, respectively. The hybrid magnetron deposited (Ti,Cr)-Al-C coatings can be used to protect interconnects in lightweight molten carbonate fuel cells elements.